EPISTEMOLOGI HADIS: Melacak Sumber Otentitas Hadis - Atabik, Ahmad (IAIN Pekalongan, 2010)
﻿Quran and Hadith have different historical side. This different implicates the differences of science development affiliated with them. One of them, that are very significant, is their link from the period of the prophet Mohammad to us. Quran as the first source of Islamic teaching –no doubt– comes to us by tasalsul or tawâtur (handed down from person to person for generations). Hadith, on the other hand, if it is examined carefully, has only little that is tawâtur, and most of them can be said as Hadith âhâd. In this paper, I will try to examine the epistemological side of Hadith. How to know its link from the Prophet to us? Certainly, a tool that is able to bridge and examine the problems around the first source or the Prophet period that is out of our coverage is needed. I give some suggestions to know it. Two of them are the isnâd or sanad system and the concept of tawâtur. The existence of sanad and its tawâtur, will, of course, clarify the position of the text or the source of Islamic teaching is really from the Prophet as a messenger.